Development of a colloidal gold immunoassay for the detection of four eugenol compounds in water - Xinyi Shen; Xiaoling Wu; Liqiang Liu; Hua Kuang (Food and Agricultural Immunology, 2019)
A monoclonal antibody (mAb), 2C9, selective for four eugenol compounds, was developed based on the eugenol derivatives (Eug-1). The semi-inhibitory concentrations (IC50) of this antibody against eugenol, isoeugenol, methyl eugenol, and methyl isoeugenol were 0.043, 0.302, 0.016, and 0.082 μg/mL, respectively, and the detection limits (LOD) were 0.012, 0.070, 0.004 and 0.024 μg/mL. With the exception of isoeugenol, which had cross-reactivity of less than 15%, the cross-reactivity of the other compounds was good, ranging from 52.4% to 269%. In the ic-ELISA recovery test, recovery was between 80% and 94%, indicating that the method was suitable for analysis of eugenol compounds in water. The cut-off values of the immunochromatographic strips for the four compounds in water were 5, 100, 100, and 100 μg/mL, respectively, indicating that the ic-ELISA and immunochromatographic strips we developed can be used to rapidly detect eugenol compounds in water.